HUSAIN AL-HALLAJ DAN AJARANNYA - zainuddin Hamkah (Fakultas Agama Islam Universitas Islam Makassar (UIM), 2018)
Al-Hallaj is having the full name of Abu Al-Mughis Al-Husayn Ibn Mansur Ibn Muhammad Al Baidawi. Grandson of Muhammad which before his grandfather was converted to Islam, his grandfather was a Buddhist worshiper. But there is also a saying that al-Hallaj is descended from Abu Ayyub, one of the companions of Prophet Muhammad SAW. From other literature Al-Hallaj has the full name of Hussein bin Mansur Al-Hallaj. Born in 244 H or 858 CE in one of the small towns of Persia, namely the city of Baidha. Al-Hallaj is the pioneer of the teachings of al-hulul, a doctrine which states that God chooses the human body to dwell if man is capable of removing his human nature (nasut). For man has the nature of divinity (lahut) as well as God who has the nature of humanity in addition to the nature of His Godhead. al-Hallaj when he reaches the level of hulul, he is not lost or destroyed, but two forms united in one body. And this process takes place with God's way down to earth in the body of al-Hallaj. The teachings of al-Hulul brought by al-Hallaj this reap an awkwardness for other scholars, for example Sheikh Abu Nasr as-Sarraj, once said: